Remote Sensing Of Pm10 From Landsat Tm Imagery. - H., S. Lim; MatJafri, M. Z.; Abdullah, K.; Saleh, N. M.; AlSultan, Sultan (2004)
Air pollution concentration has been estimated over Penang Island from Landsat TM 7. In-situ measurements of the corresponding air pollution parameter (particulate matter less than 10 micron, PM10) were carried out simultaneously with the acquisition of the satellite imagery.